2017
DOI: 10.1002/jbm4.10008
|View full text |Cite
|
Sign up to set email alerts
|

Flare‐Up After Maxillofacial Surgery in a Patient With Fibrodysplasia Ossificans Progressiva: An [18F]‐NaF PET/CT Study and a Systematic Review

Abstract: Fibrodysplasia ossificans progressiva (FOP) is a rare genetic disorder leading to progressive heterotopic ossifications (HO) of muscles, tendons, and ligaments, which can be induced by trauma or by surgery. Despite strong medical advice to the contrary, an FOP patient insisted on surgery to alleviate her complete trismus, which caused an unbearable impact on her quality of life (QOL). The entire trismus history of this FOP patient is presented. [18F]‐NaF position emission tomography/computed tomography (PET/CT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0
1

Year Published

2018
2018
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 11 publications
1
26
0
1
Order By: Relevance
“…FOP patients may experience multiple flare‐ups and HO lesions across time and, in some instances, within the same anatomical location . Apart from the direct trauma flare‐ups can have on nervous system pain pathways and the peripheral structures they innervate, the occurrence of multiple flare‐ups likely alters the functionality of pain systems both in the periphery and central nervous system (CNS).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…FOP patients may experience multiple flare‐ups and HO lesions across time and, in some instances, within the same anatomical location . Apart from the direct trauma flare‐ups can have on nervous system pain pathways and the peripheral structures they innervate, the occurrence of multiple flare‐ups likely alters the functionality of pain systems both in the periphery and central nervous system (CNS).…”
Section: Discussionmentioning
confidence: 99%
“…FOP patients may experience multiple flare-ups and HO lesions across time and, in some instances, within the same anatomical location. (21)(22)(23) Apart from the direct trauma flare-ups can have on nervous system pain pathways and the peripheral structures they innervate, the occurrence of multiple flare-ups likely alters the functionality of pain systems both in the periphery and central nervous system (CNS). Taken together, the effect of flare-up episodes is likely cumulative; potential outcomes of these pathologic events include a facilitation of a chronic pain background or flare-ups become more painful as they occur in later years of life.…”
Section: Discussionmentioning
confidence: 99%
“…This will also allow quantitation of bone formation. Other related assessments, such as 18 F sodium fluoride positron emission tomography (PET)/CT can also be considered ; however, availability may be limited in some institutions. Where alternate scores or measures are used, these need to be demonstrated to be at least equivalent in performance to the recommended measures, and ideally have known and close correlation with the recommended measures.…”
Section: Resultsmentioning
confidence: 99%
“…Whether radiotherapy can cause sufficient trauma to trigger a flare-up, leading to HO, is unclear. Previously, we have demonstrated that [ 18 F]NaF PET can be used to detect activity of disease just prior to the formation or progression of HO (4)(5)(6). Intravenously administered labeled sodium fluoride ([ 18 F]NaF) binds to newly formed hydroxyapatite and, therefore, can be used to detect osteoblastic activity (7).…”
Section: Introductionmentioning
confidence: 99%